Analisis Pemanfaatan Serbuk Gergaji Kayu Dan Egg Tray Sebagai Bahan Alternatif Tahan Panas Pada Genset - Simangunsong, Kristian Jubatner; Napitupulu, Robert; Yuliyanto, Yuliyanto (Jurnal Inovasi Teknologi Terapan, 2025)
Technological developments have encouraged the use of generator sets as an alternative source of electricity, but this also causes problems, such as excessive heat production that disrupts comfort in the work area. This study aims to utilize sawdust and egg tray waste as heat-insulating materials for generator sets. Sawdust, which is often discarded, can be utilized to reduce the negative impacts of using generator sets and overcome environmental pollution caused by this waste. Previous studies have shown that the combination of sawdust and starch at certain temperatures can produce products with good compressive strength. The results of the ANOVA analysis in this study showed that the volume fraction of 35%: 15% with a thickness of 20 mm gave the highest heat absorption coefficient of 43.06°C, while the volume fraction of 40%: 10% with a thickness of 10 mm produced the lowest value of 35.8°C. These findings emphasize the importance of selecting volume fractions and thicknesses in increasing heat absorption efficiency, as well as providing alternative solutions for the management of sawdust and egg tray waste.